Normative Tensions between International Law and Customary Legal Systems: Comparative Insights from Indonesia and Spain - Zamrud, Wa Ode; Pozo, Antonio Gutiérrez (Faculty of Law, Universitas Pattimura, 2026)
Introduction: This article examines the normative tension between international law and customary legal systems within the framework of global legal pluralism. It highlights how universal principles such as self-determination, human rights, and the rule of law interact with local values grounded in spirituality, social balance, and communal legitimacy. Within this context, the incorporation of global norms into local legal systems often generates epistemological and ideological frictions that influence the structure and legitimacy of national law. Purposes of the Research: This research aims to analyze the forms and characteristics of normative tensions between international law and customary legal systems in Indonesia and Spain. Furthermore, it seeks to examine the legal approaches adopted by both countries in negotiating the relationship between international legal norms and local values. Methods of the Research: This study employs a normative legal research method using a comparative approach and a conceptual approach. The focus of analysis lies in the examination of norms, principles, and legal doctrines governing the relationship between international law and customary legal systems. Data were processed through inventory, classification, and systematization, and analyzed using a qualitative-descriptive method combined with deductive reasoning to formulate normative conclusions. Results of the Research: The findings reveal that normative tensions in Indonesia exhibit an asymmetrical translation, where the state functions as a dominant filter that often reduces customary values into administrative norms. In contrast, in Spain, the tension manifests as horizontal-institutional, as the interaction between international norms and regional customary law (fuero) occurs through constitutional mechanisms. Indonesia demonstrates a negotiation pattern through a contextual universalism model, emphasizing the internalization of global values within the moral and spiritual framework of customary law. Meanwhile, Spain applies institutional pluralism through its system of regional autonomy. The novelty of this research lies in the proposition of an Adaptive Legal Pluralism Framework as a new paradigm for harmonizing international law and customary law based on inter-normative dialogue and respect for local legitimacy.